Effects of Polycarboxylate-Lignosulfonate Superplasticizer on the Engineering Properties and Cementitious Paste Thickness of Pervious Concrete - Ehsan Teymouri; Nurul Noraziemah Mohd Pauzi; Wong Kwong Soon; Mehdi Forouzan; Marjan Salari (Journal of Rehabilitation in Civil Engineering)
This study investigates the effects of polycarboxylate-lignosulfonate superplasticizer (PLS), water, and cement content on mechanical, physical and cementitious paste thickness of pervious concrete (PC) for its further application in urban areas. For this reason, 17 PC mixtures containing different portions of PLS (0.10% to 1.00% of the cement content), water-to-cement ratio (0.30 to 0.40), and cement content (315 to 350 kg/m3) with a constant range aggregate size (4.75 to 9.5 mm) were designed, tested, and analyzed by Design of Expert (DoE). The results showed that increasing the proportion of PLS, water, and cement increased the compressive strength of PC at ages of 7, 11, and 28 days. However, the permeability and porosity would decrease due to formation of a pasty mixture. The effect of water content on changing the compressive strength was more significant than other variables, especially in the range of 0.3 to 0.35. Apart from this, increasing the portion of variables resulted in increasing the average cementitious paste thickness and the number of line segments, which both resulted in an increment of compressive strength. The PC mixture with 1.00% of PLS, W/C ratio of 0.40, and cement content of 350 kg/m3 had the maximum compressive strength of 18.35 MPa with reasonable porosity and permeability. This system is suitable as pavements in urban areas with light-traffic load, green spaces, and sidewalks to mitigate the anthropization impacts.